2015
DOI: 10.1186/s13006-015-0041-x
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of early feeding on growth velocity and overweight/obesity in a cohort of HIV unexposed South African infants and children

Abstract: BackgroundSouth Africa has the highest prevalence of overweight/obesity in Sub-Saharan Africa. Assessing the effect of modifiable factors such as early infant feeding on growth velocity and overweight/obesity is therefore important. This paper aimed to assess the effect of infant feeding in the transitional period (12 weeks) on 12–24 week growth velocity amongst HIV unexposed children using WHO growth velocity standards and on the age and sex adjusted body mass index (BMI) Z-score distribution at 2 years.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…This is evidenced by the high number of HIV/ PMTCT infant and young child feeding studies included in this review (n = 14 articles). 11,20,22,23,25,[27][28][29][30][31][32][33][34][35] However, the results on breastfeeding practices found by this review need to be interpreted against the existing policy background and the changes made in HIV and infant feeding guidelines in South Africa. The practice of giving free formula might have influenced more mothers to choose to formula feed and might have made formula feeding more acceptable in communities.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This is evidenced by the high number of HIV/ PMTCT infant and young child feeding studies included in this review (n = 14 articles). 11,20,22,23,25,[27][28][29][30][31][32][33][34][35] However, the results on breastfeeding practices found by this review need to be interpreted against the existing policy background and the changes made in HIV and infant feeding guidelines in South Africa. The practice of giving free formula might have influenced more mothers to choose to formula feed and might have made formula feeding more acceptable in communities.…”
Section: Resultsmentioning
confidence: 89%
“…Cereal based foods were the most popular type of complementary food (13 studies)-specifically maize meal porridge (sometimes described as soft and thin), and commercial infant cereal 10,[12][13][14][15]17,19,20,21,36,37,39,41 (6) Use of water and other non-milk liquids Water was commonly given to infants before 6 months (10 studies) 1,11,12,15,19,20,30,32,36,39 Black tea, rooibos tea, sugar water, traditional herb mixtures, gripe water, antacid preparations and ijuba (a sorghum beer) were also given to children from birth 11,12,14,19,20,36 (7) Foods of concern Processed meats, soft drinks, sweets and salty crisps were some of the foods being given to older infants and young children that are cause for concern 13,14,17 (8) Meal frequency Only four studies reported on the total number of feeds per day:…”
Section: Criteria Findingmentioning
confidence: 99%
“…If implemented globally at near universal levels (> 90%), optimal breastfeeding practices could reduce global child deaths by more than 800,000 [ 3 ], which makes breastfeeding the most effective preventive intervention to improve infant mortality [ 4 ]. The numerous benefits of breastfeeding continue to accrue throughout childhood and into adulthood, including reduced morbidity from diarrhoeal and respiratory illness [ 5 ], and reduced risk of overweight and obesity in children, another of the six UN targets [ 1 , 6 ]. Although long term follow-up studies on infant feeding practices have implicit methodological challenges [ 7 ], the favourable effect of breastfeeding on cognitive performance indicators has recently been presented [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) published growth velocity standards in 2009, 15 offering the opportunity to score weight and length gain according to age and sex. Two studies have used the WHO growth velocity standards to assess the relationship with future nutritional status, but one focused on the association with obesity and did not compare the predictive ability of weight velocity with other growth measures, 16 and the other studied children with cystic fibrosis in the US. 17 Studying growth velocities could help to identify critical time windows for prevention or early interventions of undernutrition.…”
mentioning
confidence: 99%